2013
DOI: 10.1016/j.jmoldx.2013.05.007
|View full text |Cite
|
Sign up to set email alerts
|

A Multiplex qPCR Gene Dosage Assay for Rapid Genotyping and Large-Scale Population Screening for Deletional α-Thalassemia

Abstract: The predominant determinants of α-thalassemia are deletions in the human α-globin gene cluster. A rapid DNA-based assay is needed for mass screening in thalassemia-prevention programs. Herein, we established a novel quadruplex TaqMan qPCR gene dosage assay with two separate combination reactions. The assay directly determined the copy number of human α-globin genes based on relative quantitation of three target genes (HBA2, HBA1, and HBZ or HBPA1) versus a control gene (CREBBP). The assay showed good accuracy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…All PCR reactions used the following conditions: 94˚C for 3 min followed by 40 cycles at 94˚C for 30 sec and 72˚C for 45 sec. The data were analyzed using the ΔΔCq method (21), with β-actin as the internal control. The primer sequences, the expected PCR product sizes (base pairs; bp), and the annealing temperatures were as follows: mTOR, sense 5'-TGT CGA GAG GCA ACA ACC TC-3' and antisense 5'-TTG TTG GCT GCA TTG TGA CG-3' (298 bp, 60˚C); p70S6K, sense 5'-GGA TTT CTG GGG ACG AGG TG-3' and antisense 5'-AGA GTT GGG CTG TCG GAT TG-3' (148 bp, 58˚C); tau, sense 5'-CTG AAG AAG CAG GCA TCG GA-3' and antisense 5'-GGT GGT TCA CCT GAT CCT GG-3' (265 bp, 59˚C); caspase-3, sense 5'-CGG ACC TGT GGA CCT GAA AA-3' and antisense 5'-TAA CCG GGT GCG GTA GAG TA-3' (216 bp, 60˚C); β-actin, Statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…All PCR reactions used the following conditions: 94˚C for 3 min followed by 40 cycles at 94˚C for 30 sec and 72˚C for 45 sec. The data were analyzed using the ΔΔCq method (21), with β-actin as the internal control. The primer sequences, the expected PCR product sizes (base pairs; bp), and the annealing temperatures were as follows: mTOR, sense 5'-TGT CGA GAG GCA ACA ACC TC-3' and antisense 5'-TTG TTG GCT GCA TTG TGA CG-3' (298 bp, 60˚C); p70S6K, sense 5'-GGA TTT CTG GGG ACG AGG TG-3' and antisense 5'-AGA GTT GGG CTG TCG GAT TG-3' (148 bp, 58˚C); tau, sense 5'-CTG AAG AAG CAG GCA TCG GA-3' and antisense 5'-GGT GGT TCA CCT GAT CCT GG-3' (265 bp, 59˚C); caspase-3, sense 5'-CGG ACC TGT GGA CCT GAA AA-3' and antisense 5'-TAA CCG GGT GCG GTA GAG TA-3' (216 bp, 60˚C); β-actin, Statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…To conduct this study, multiplex ligation-dependent probe amplification (MLPA) assays were performed to identify a possible unknown deletion in the α-globin gene cluster. 7 Interestingly, we found that the proband had both the --SEA deletion and a novel deletion upstream of the α-globin gene ( Figure 2C), which was further tested by next-generation sequencing (NGS) for precisely defining the location of this novel deletion ( Figure 2D). The breakpoint of this deletion was confirmed by direct PCR amplification of about 800-bp products ( Figure 2E LETTER TO THE EDITOR of this novel deletion encompassed in the α-globin gene expression enhancer HS-40 that is an important binding region for numerous transcription factors.…”
Section: A Combination Of the (αα) Gz And --Sea Deletions Causing A Smentioning
confidence: 99%
“…Deletions in the human α-globin gene cluster which have a high incidence in south China were investigated by a quadruplex TaqMan qPCR gene dosage assay. 6 Sanger sequencing was performed to detect mutations in HBB gene (PCR primers were as follow: forward primer 5′-AACTCCTAAGCCAGTGCCAGTGCCAGAAGAGC-3′; reverse primer 5′-ATGCACTGACCTCCCACATTCCCT-3′). MLPA kits (MRC-Holland, Amsterdam, the Netherlands) were used to identify rearrangements in the beta-globin gene cluster (SALSA MLPA KIT P102 HBB).…”
Section: Molecular Analysismentioning
confidence: 99%